Structural alloys for power plants operational challenges and high-temperature materials - Shirzadi, A.; Jackson, S. (Woodhead Publishing in energy, 2014)
Current fleets of conventional and nuclear power plants face increasing hostile environmental conditions due to increasingly high temperature operation for improved capacity and efficiency, and the need for long term service. Additional challenges are presented by the requirement to cycle plants to meet peak-load operation. This book presents a comprehensive review of structural materials in conventional and nuclear energy applications. Opening chapters address operational challenges and structural alloy requirements in different types of power plants. The following sections review power plant structural alloys and methods to mitigate critical materials degradation in power plants.